ANALISIS TANTANGAN DAN KONTRIBUSI PASAR MODAL SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Siti Parida Dwi Yuliantika, Ana; Jelita, Jelita; Ramadhani dg. Matutu, Rizqy; Cahyaningrum, Eko (At-Tawazun, Jurnal Ekonomi Syariah, 2024)
This study aims to examine the development and regulation of the sharia capital market in Indonesia, as well as its impact on economic growth. The Islamic capital market is increasingly in demand by Muslim investors because of its adherence to sharia principles, which also increases market stability and liquidity. The method used in this study is library research which is carried out by collecting information and data through various sources available in the library. both related to laws, fatwas, books, reports, and relevant scientific publications. The findings of the study show that the Islamic capital market in Indonesia has made a major contribution to economic growth, by recording an increase in market capitalization, the number of sharia stocks, sharia bonds (sukuk), and sharia mutual funds. This development reflects investor confidence and the attractiveness of the Islamic capital market as an alternative investment that is in line with Islamic principles. In addition, the Islamic capital market also plays a role in funding the real sector, including MSMEs, through the Securities Crowdfunding (SCF) scheme, which further strengthens its contribution to the Indonesian economy.